Undergraduate students' performance: the case of University of Malaya - Alfan, Ervina; Othman, Md Nor (Emerald, 2005)
Purpose - The purpose of this study is to determine the undergraduate students' performance in the Faculty of Business and Accountancy, University of Malaya and the factors influencing the performance of the undergraduate students. Design/methodology/approach - The performance of the undergraduate students in this study is measured by their cumulative grade point average (CGPA) in the final semester. In this study, the students' demographic profile, entry qualifications and the subjects taken by the students in pre-university level are used as the predictor variable for the students' performance in the degree programme. Findings - The result of the study shows that the predictor variables do explain the variance in the students' final CGPA. In addition, it was found that knowledge prior to entering the university such as economics, mathematics and accounting is crucial in assisting the students in undertaking the courses in both business and accounting programme. The study also found that female students perform better than male students; whilst Chinese students perform better than Malay and Indian students. Research limitations/implications - The implications of this study for the academics in universities and schools are also discussed in the paper. This paper, however, does not look into variables other than students' past performance prior to entering the university that may have an influence over the students' performance in the university. Hence, this aspect may be examined in future researches. Originality/value - This paper will be useful to the academic communities, the public and other interested parties who are interested in improving students' performance during their periods of study in the universities. © Emerald Group Publishing Limited.